2016
DOI: 10.1039/c5tb02191j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field responsive drug release from magnetoliposomes in biological fluids

Abstract: The final fate of nano-scaled drug delivery systems into the body is highly affected by their interaction with proteins in biological fluids (serum, plasma, etc.). Nanocarriers dispersed in biological fluids bear a protein ''corona'' that covers their surface. Thus, it is extremely important to evaluate the drug release efficiency also in the biological environment where protein-nanocarrier complexes are formed. The purpose of this work is to determine how drug release from lipid vesicle carriers is influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…In this aspect, Lundqvist et al [ 31 ] have reported that even for a specific material type, the size of the particle, and its surface modification can completely alter the protein corona and probably their biological impact. Corona proteins can physically mask the nanoparticle surface, potentially affecting the therapeutic effect of the molecules bound to the nanoparticle surface [ 32 ]. On another hand, it has also been described that cellular uptake is strongly related to the nature of the proteins that constitute protein corona [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, Lundqvist et al [ 31 ] have reported that even for a specific material type, the size of the particle, and its surface modification can completely alter the protein corona and probably their biological impact. Corona proteins can physically mask the nanoparticle surface, potentially affecting the therapeutic effect of the molecules bound to the nanoparticle surface [ 32 ]. On another hand, it has also been described that cellular uptake is strongly related to the nature of the proteins that constitute protein corona [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such anomalous behaviour has been attributed to vesicle destabilization and subsequent healing of the system. 26 In another experiment. the system was sonicated for different periods of times at 293.15 K and percent urea release obtained as a function of time is presented in Fig.…”
Section: Urea Release From Microvesiclesmentioning
confidence: 94%
“…A study demonstrated selective hypothermia in vivo and in vitro using magnetoliposomes under a low-frequency AMF to promote lipid membrane permeability from local heating. However, the relatively high heating of the composite particles led to concerns of overheating normal body tissues [142]. In order to overcome injury to healthy tissues caused by the overheating of the particles, other groups embedded the MNPs within the drug carrier to minimize heating of the tissue directly for their drug release studies.…”
Section: Magnetism For Triggered Drug Releasementioning
confidence: 99%